Safety assessment of crude saponins from Chenopodium quinoa willd. husks: 90-day oral toxicity and gut microbiota & metabonomics study in rats. (1st May 2022) - Zhang, Ruoyu; Zhai, Qingfeng; Yu, Yuan; Li, Xuening; Zhang, Fengxiang; Hou, Zhaohua; Cao, Yuqing; Feng, Jing; Xue, Peng
Graphical abstract: Highlights: Limited subchronic toxicity of quinoa saponin provided new idea of its utilization. Excessive intake of quinoa saponin has been proved to damage the gut tract. Quinoa saponins led to the change of gut microbiota and metabolism in in vivo study. Abstract: The subchronic toxicity of saponins of Chenopodium quinoa Willd. husks in healthy adult Sprague-Dawley (SD) rats was explored. Female and male rats were randomly divided into 0, 5, 50, and 500 mg/kg body weight (BW)/day groups. Subchronic general toxicity, metabonomics and gut microbiota were assessed. The rats treated with saponins weighed less and had lower blood sugar levels ( P < 0.05). Thirty-two differential metabolites were found in female rats and 23 in male rats. Saponins also led to changes in metabonomics. Slight necrosis was observed in the intestinal mucosa, which was associated with an increase in the gut microbiota diversity of female rats in the high-dose saponin treatment group and metabolic changes in the liver and kidney. In conclusion, the toxic effect of quinoa saponins is sex-dependent; however, the no-observed-adverse-effect level for quinoa saponins was evaluated to be under 50 mg/kg BW/day for both sexes in the current study.